The Valuation Performance of Mathematically-Optimised, Equity-Based Composite Multiples - Soon Nel; Niël Johannes Le Roux (Journal of Economics, Finance and Administrative Science, 2017)
Purpose – This paper aims to examine the valuation precision of composite models in each of six key industries in South Africa. The objective is to ascertain whether equity-based composite multiples models produce more accurate equity valuations than optimal equity-based, single-factor multiples models. Design/methodology/approach – This study applied principal component regression and various mathematical optimisation methods to test the valuation precision of equity-based composite multiples models vis-à-vis equity-based, single-factor multiples models. Findings – The findings confirmed that equity-based composite multiples models consistently produced valuations that were substantially more accurate than those of single-factor multiples models for the period between 2001 and 2010. The research results indicated that composite models produced up to 67 per cent more accurate valuations than single-factor multiples models for the period between 2001 and 2010, which represents a substantial gain in valuation precision. Research implications – The evidence, therefore, suggests that equity-based composite modelling may offer substantial gains in valuation precision over single-factor multiples modelling. Practical implications – In light of the fact that analysts' reports typically contain various different multiples, it seems prudent to consider the inclusion of composite models as a more accurate alternative. Originality/value – This study adds to the existing body of knowledge on the multiples-based approach to equity valuations by presenting composite modelling as a more accurate alternative to the conventional single-factor, multiples-based modelling approach.
Keywords: L83; 330; Emerging markets; Composite multiples; Equity multiples; Equity valuations; Valuation precision